Core Competences in the Knowledge-Based Theory of the Enterprise - Sankowska, Anna (Kluczowe kompetencje w teorii zasobowej przedsiębiorstwa, 2010)
This article concerns the issue of core competences, which springs from the resources-based theory of the company. There was presented the place of core competences in the resources-based theory with connection to knowledge and an attempt to examine its understanding in the literature. In addition, there were described empirical research results revealing the level of core competences concentration in innovative enterprises.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 133, s. 114-121
Keywords: core competences; knowledge-based theory of the enterprise; innovativeness